Retardo do envelhecimento cronológico pela restrição calórica e a ficocianina em células de saccharomyces cerevisiae mutantes ao gene sir - Santolin, Marta Beatriz (2012)
The aging process is accompanied by changes in the activity of the cells, tissues and organs. The progressive accumulation of these changes is associated with the increasing of susceptibility to disease that accompanies advancing age. The interest in developing anti-aging therapies is increasing considerably; however many contributions in this line of research are still needed. Caloric restriction has been reported to prevent the onset of chronic diseases related to aging and prolong life in different experimental models. It is a form of nutritional intervention widely discussed to extend the lifetime in a variety of species, including humans. The use of molecules with functional capacity has received attention, since studies suggest an inverse relationship between intake of these compounds and the incidence of diseases related to aging. In this context, this study aimed to analyze the role of phycocyanin and caloric restriction in chronologically aging yeast cell Saccharomyces cerevisiae. To this end, we used the yeast strains control (BY4741) and the deleted genes sir1, sir2, sir3 and sir4. Cells were grown in YPD medium 2 % glucose (P), glucose 2 % YPD phycocyanin + (P + PC), when exposed to 0.01 mg/ml of phycocyanin, YPD for 1 h and 0.5 % glucose (RC). The strains were subjected to 24 hours of aging and collected for analysis of cell survival and lipid peroxidation. The use of caloric restriction and phycocyanin therapy showed benefit in the percentage of cell survival and lipid peroxidation. The results indicate that the sir2 gene-deleted strain showed greater sensitivity to treatment with caloric restriction and phycocyanin. Lipid peroxidation was attenuated by the use of therapies Caloric restriction and phycocyanin in all strains studied no statistically significant differences. This finding allows us to suggest that these proteins may be influenced by diet or by the use of antioxidants, becoming interesting therapeutic targets for diseases due to aging. However, there are important questions that need to be elucidated to improve understanding of the mechanisms of sirtuins and their therapeutic potential